# Trigonometry

posted by .

Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b in terms of sinx and cosx.

I don't know what i'm supposed to do, and i don't come to an answer! Help, thanks!

my workings:

tan(45+x)= (1+tanx)/(1-tanx)
a/b = (1+tanx)/(1-tanx)
a(1-tanx)=b(1+tanx)
i square both sides...
a^2(1-tanx)^2 = b^2(1+tanx)^2
a^2 + b^2 = 2
a^2 = 2 - b^2
substitute:
(2-b^2)(1-tanx)^2 = b^2(1+tanx)^2

I don't know if im on the right track, but i don't seem to come to an answer when i expand the whole equation!

• Trigonometry -

From:
a(1-tanx)=b(1+tanx)
multiply both sides by cos(x) to get
a(cos(x)-sin(x))=b(cos(x)+sin(x))
Now square and simplify. The product terms will cancel out after you substitute b²=(2-a²) to give you a in terms of sin(x) and cos(x).
You can do similarly for b.

## Similar Questions

1. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
2. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
3. ### Trig........

I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top and …
4. ### Trigo

Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b in terms of sinx and cosx. I don't know what i'm supposed to do, and i don't come to an answer! Help, thanks! my workings: tan(45+x)= (1+tanx)/(1-tanx) a/b = (1+tanx)/(1-tanx) …
5. ### maths - trigonometry

I've asked about this same question before, and someone gave me the way to finish, which I understand to some extent. I need help figuring out what they did in the second step though. How they got to the third step from the second. …
6. ### TRIGONOMETRY *(MATHS)

Q.1 Prove the following identities:- (i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii) (1+cotx+tanx)(sinx-cosx)/sec^3x-cosec^3x = sin^2xcos^2x.
7. ### Trigonometry Check

Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] = [cosx(1-sinx]/[cosx(1+tanx] …
8. ### trigonometry

can i use factoring to simplify this trig identity?
9. ### Trigonometry

Prove the following trigonometric identities. please give a detailed answer because I don't understand this at all. a. sin(x)tan(x)=cos(x)/cot^2 (x) b. (1+tanx)^2=sec^2 (x)+2tan(x) c. 1/sin(x) + 1/cos(x) = (cosx+sinx)(secx)(cscx) d. …
10. ### Trigonometry

How do you simplify: (1/(sin^2x-cos^2x))-(2/cosx-sinx)?

More Similar Questions